How much parents of pre-school children know about speech disorder prevention, based on research - Grzesiak-Witek, D.; Puk, M. (Psychological Counseling and Psychotherapy, 2017)
Theoretical part of the article deals with secondary prophylaxis of speech disorders, which includes early children identification of the high-risk group. Tertiary level is oriented on supportive and developing actions for children with diagnosed speech problems. Parents as being the first caregivers, are particularly responsible for any disorders prophylaxis including speech dysfunction. As our study reveals in general parents knowledge level of the child’s speech development are mostly satisfactory. However, there are also a group of patents who could not define properly child normal or pathological speech development in preschool period. We confirm the idea of involving mass media and all child specialists (teachers, therapists in kindergartens,nursery staff, any preschool institutions and hospital) to joint measures in providing educational competence in speech development by radio and TV programs, brochures, magazines, posters, seminars and workshops for better health care.